ANALYSIS OF FACILITY ACCESSIBILITY NEED FOR IMPROVING SERVICES FOR PASSENGERS WITH DISABILITIES - Nur Syaifudin, Dika; Rochmawati, Laila; Muti Sazali, Abdul; Silk Moonlight, Lady; Musadek, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Kalimarau Airport is an airport located in Teluk Bayur District, Berau Regency, East Kalimantan. Where at the Kalimarau airport terminal there are facilities for the public and for passengers with disabilities. As for the services provided in the form of assistance to make it easier for passengers with disabilities to communicate and move from the check-in process to the passengers with disabilities to carry out the boarding process. So that by providing the facilities and services that have been provided, the purpose of this study is to determine the ideal readiness of facilities and services as well as the availability of facilities for passengers with disabilities. In this study the authors used a quantitative research method. For data collection techniques using documentation, observation, interviews, and questionnaires. Whereas in processing the data from the questionnaire results the author uses validity test data and reliability test data, The final results achieved from this study indicate that for the results of the validity test all items obtained a value greater than the r table value, namely 0.344 which was declared valid and for the reliability test results obtained a value of 0.970 which was in the high category. So that a conclusion can be drawn where there are still deficiencies in fulfilling the accessibility of facilities for passengers with disabilities, while the availability of facilities and services that have been provided are quite good.